A training programme to build cancer research capacity in low- and middle-income countries: findings from Guatemala - Lauren D Arnold; Joaquin Barnoya; Eduardo N Gharzouzi; Peter Benson; Graham A Colditz
Problem Guatemala is experiencing an increasing burden of cancer but lacks capacity for cancer prevention, control and research. Approach In partnership with a medical school in the United States of America, a multidisciplinary Cancer Control Research Training Institute was developed at the Instituto de Cancerología (INCAN) in Guatemala City. This institute provided a year-long training programme for clinicians that focused on research methods in population health and sociocultural anthropology. The programme included didactic experiences in Guatemala and the United States as well as applied training in which participants developed research protocols responsive to Guatemala's cancer needs. Local setting Although INCAN is the point of referral and service for Guatemala's cancer patients, the institute's administration is also interested in increasing cancer research - with a focus on population health. INCAN is thus a resource for capacity building within the context of cancer prevention and control. Relevant changes Trainees increased their self-efficacy for the design and conduct of research. Value-added benefits included establishment of an annual cancer seminar and workshops in cancer pathology and qualitative analysis. INCAN has recently incorporated some of the programme's components into its residency training and established a research department. Lessons learnt A training programme for clinicians can build cancer research capacity in low- and middle-income countries. Training in population-based research methods will enable countries such as Guatemala to gather country-specific data. Once collected, such data can be used to assess the burden of cancer-related disease, guide policy for reducing it and identify priority areas for cancer prevention and treatment.